Valuasi Ekonomi Terhadap Penyedia Jasa Wisata Alam di Taman Hutan Raya Sultan Adam - Indah Lestari; Noor Rahmini (JIEP: Jurnal Ilmu Ekonomi dan Pembangunan, 2022)
This study aims to determine the factors that affect the number of visits and the economic value of the Tahura Sultan Adam tourism object. Data collection techniques are observation and interviews with a questionnaire. The data were processed using descriptive analysis, multiple linear regression, and the consumer surplus formulae. From the research, it is known that the characteristics and perceptions of visitors vary widely, consisting of age, regional origin, gender, marital status, education level, occupation, total income, type of vehicle, number of groups, information about tourist attractions, tourist attractions, motivation, additional facilities, security, officer services, accessibility, cleanliness, air pollution, admission tickets, and willingness to pay. The collected data were analyzed using multiple linear regression analysis models. From the research results, three factors significantly affect the number of visits to Tahura Sultan Adam, namely income, travel costs, and length of travel. From the calculation, results can be seen in surplus-value consumer travel cost method individual visitation Rp 179 153 and subsequently obtained the economic value of Rp 17,610,381,594 annually